2017
DOI: 10.1371/journal.pone.0178000
|View full text |Cite
|
Sign up to set email alerts
|

Prediabetes is associated with the modulation of antigen-specific Th1/Tc1 and Th17/Tc17 responses in latent Mycobacterium tuberculosis infection

Abstract: Type 2 diabetes mellitus (DM) is associated with the down modulation of Th1, Th2 and Th17 responses in latent Mycobacterium tuberculosis infection but the role of prediabetes (PDM) in this setting is not well understood. To examine the role of CD4+ and CD8+ T cell cytokines in latent tuberculosis (LTB) with coincident PDM, we studied the baseline, mycobacterial, control antigen and mitogen–stimulated T cell cytokine responses in LTB individuals with (LTB-PDM; n = 20) or without (LTB-NDM; n = 20) concomitant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…Immunological differences in DM-TB compared to TB only include enhanced proinflammatory responses [ 12 ], and increased circulating cytokines have also been described in IH-TB [ 41 ]. Immune abnormalities are detectable in individuals latently infected with M. tuberculosis with IH [ 42 ], and it is possible that concurrent intermediate hyperglycemia and latent TB infection drives the development of both diseases, in a similar manner to the synergism between TB and HIV disease. This may indicate a relationship between moderate HbA1c values and TB susceptibility that warrants careful clinical considerations, and investigation of clinical disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Immunological differences in DM-TB compared to TB only include enhanced proinflammatory responses [ 12 ], and increased circulating cytokines have also been described in IH-TB [ 41 ]. Immune abnormalities are detectable in individuals latently infected with M. tuberculosis with IH [ 42 ], and it is possible that concurrent intermediate hyperglycemia and latent TB infection drives the development of both diseases, in a similar manner to the synergism between TB and HIV disease. This may indicate a relationship between moderate HbA1c values and TB susceptibility that warrants careful clinical considerations, and investigation of clinical disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize the role of CD4 + and CD8 + T‐cell cytokines in LTB with coincident PDM, Kumar et al . studied the baseline, mycobacterial antigen and mitogen‐stimulated T‐cell cytokine responses in LTB individuals with (LTB‐PDM) or without (LTB‐NDM) concomitant PDM.…”
Section: Effect Of Pre‐diabetes In Tb Patientsmentioning
confidence: 99%
“…γδ T cells can produce Th1 (TNFα, IFNγ) cytokines which are crucial for immune protection against viruses and intracellular microbes ( O’Brien et al, 2009 ; Bonneville et al, 2010 ). Our previous studies have shown that antigen-specific Th1 responses in CD4 + T cells were reduced in LTB DM and LTB PDM comorbidities ( Kumar et al, 2017 ). Our findings suggest that the frequencies of γδ T cells expressing Th1 cytokines (mainly IFNγ, TNFα) are also decreased in the LTB DM and LTB PDM groups compared to the LTB NDM group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IL-22 is produced by a wide range of cells, which includes Th1, Th17, γδ T cells, and innate immune cells like innate lymphoid cells (ILCs) ( Toussirot et al, 2018 ; Cella et al, 2019 ). Our earlier study has shown that antigen-specific Th17 responses in CD4 + T cells were reduced in LTB DM and LTB PDM comorbidities ( Kumar et al, 2017 ). Our current study demonstrates diminished frequencies of γδ T cells expressing IL-17 family cytokines in LTB DM or LTB PDM comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation